Echocardiographic Abnormalities in Children with Chronic Kidney Disease on Maintenance Hemodialysis - Adnan, Aneeqa; Akhtar, Naureen; Jamshaid, Abdul Ahad; Kazmi, Tehmina; Kazmi, Uzma; Chaudary, Adeela (Pakistan Armed Forces Medical Journal, 2022)
Objective: To identify the echocardiographic abnormalities in children with chronic kidney disease on maintenance hemodialysis.Study Design: Prospective longitudinal study.Place and Duration of Study: Hemodialysis unit of Department of Pediatric Nephrology, The Children’s Hospital and Institute of Child Health, Lahore from Jun to Nov 2020.Methodology: A total of 75 children of chronic kidney disease on hemodialysis were included. Blood and urine tests, chest x-ray and transthoracic echo cardio-grapy were performed to assess the cardiac morphological and functional abnormalities. Results: The mean age of patients was 12.14 ± 2.18 years with 54 (72%) males and 21 (28%) females. The mean duration of hemodialysis was 22.54 ± 17.01 months with mean urea reduction ratio (URR) (%) 65.58 ± 4.31 and mean Kt/v 1.3 ± 0.1. Hypertension was noted in 70 (93.3%) patients with mean systolic and diastolic blood pressure 134.07 ± 10.64 and 89.13 ± 6.78 mmHg, respectively. The echocardiography revealed the mean ejection fraction of 58.02 ± 12.40 with mild systolic and diastolic dysfunction noted in 48 (64%) patients, pericardial effusion in 23 (30.7%) cases and left ventricular hypertrophy (LVH) in 52 (69.3%) cases.Conclusion: As the frequency of left ventricular hypertrophy (LVH) was noted to be high in our chronic kidney disease patients on hemodialysis, there is a need to implement echocardiographic screening of these patients at regular intervals to identify and rectify cardiac complications early.